The Headmaster’s Support of Biology Online Learning During Covid-19 Pandemic - Ratu Berlianne Paslah; Rahmawati Darussyamsu (Jurnal Report of Biological Education, 2020)
Background: During the covid-19 pandemic, aspects of education underwent considerable change. With the release of a circular (se) ministry of education and culture of the republic of Indonesia no. 4 years 2020, our original face - to - face education is turned into long-distance or online learning. This changing learning system requires a head teacher to implement a range of policies that could support online learning in order to achieve a national education goal. The research is aimed at learning the headmaster's support of online biology during the covid-19 pandemic. Method: The study was done at the SMA Negeri 2 Pangkalpinang bases. The research method used was qualitative descriptive. Data retrieval involves a method of interviews or question-and-answer with the headmaster as a source. The data obtained were analyzed and rewritten descriptively. Results:  As a result of this study, the principal has made e-learning a solution to online learning at SMA Negeri 2 Pangkalpinang. The principal always notices the need and potential of educators and learners in developing e-learning. To support the biology study the principal supervised one of the biology teachers at the SMA Negeri 2 Pangkalpinang.